Empowerment Theory and Digital Village: Insights from West Java's Digital Village Programme - Dyana Chusnulitta Jatnika; Muhamad Burhanudin; Meilanny Budiarti Santoso; Shafira Putri Septiyanti (The Journal of Indonesia Sustainable Development Planning, 2024)
The advancement of digital technology influences rural development, requiring communities to adapt by not only relying on infrastructure but also maximizing digital technologies for social and economic empowerment. The West Java Digital Village Program serves as a case study in this research, explored through the framework of Empowerment Theory to understand its impact on individual empowerment, particularly for rural beneficiaries. This study employed qualitative methods, specifically in-depth interviews with beneficiaries of the program selected from four regencies in West Java, including Ciamis, Bandung, Sumedang, and Garut. Findings indicate that beneficiaries of the Digital Village Program experienced changes in self-concept due to increased confidence from new digital skills, along with skill development and greater perceived control. Among the indicators related to empowerment, further exploration is needed on how to create a supportive digital ecosystem in villages to maximize sustainable empowerment for beneficiaries. This research contributes to the discourse on digital transformation in rural development, offering insights for policymakers to design inclusive programs that maximize long-term benefits for rural populations.